STEREOTIP PEREMPUAN YANG DIALAMI OLEH TOKOH AMINA DALAM CERITA PENDEK AMINA KARYA SHIRLEY SAAD - Tsaniya, Faza Najmi; Prihandini, Asih (Mahadaya: Jurnal Bahasa, Sastra, Dan Budaya, 2023)
Stereotypes are stamps or labels that are often used by certain societies against women. One of the stereotypes depicted in the short story Amina by Shirley Saad is the stereotype of women. This study aims to describe the practice and impact of stereotypes on women experienced by the character Amina in the short story Amina. Stereotypes construct public perceptions of women and reinforce the stigma that women tend to be objects of labelling. The forms of negative labeling are developed from the social order internalized by women themselves. Negative labeling can have an impact on women's lives. This type of research uses qualitative methods to obtain information and depiction of stereotypes experienced by the character Amina. The data were taken from the short story entitled Amina by Shirley Saad and are using theory of feminist literary criticism. The stages of data collection are using reading, listening, and note-taking techniques to obtain relevant information. Meanwhile, the data research phase uses data analysis techniques. The results of the study show the stereotypical practice of women with negative labeling that women are baby machines, emotional, obedient, weak, and male servants. Stereotypes have a mental and physical impact, including depression, lack of confidence. and suffering. Keywords: Stereotypes, Impact, Women